Hereditary Disorders of Cardiovascular Calcification. Issue 1 (January 2021) - Rutsch, Frank; Buers, Insa; Nitschke, Yvonne
Abstract : Arterial calcification is a common phenomenon in the elderly, in patients with atherosclerosis or renal failure and in diabetes. However, when present in very young individuals, it is likely to be associated with an underlying hereditary disorder of arterial calcification. Here, we present an overview of the few monogenic disorders presenting with early-onset cardiovascular calcification. These disorders can be classified according to the function of the respective disease gene into (1) disorders caused by an altered purine and phosphate/pyrophosphate metabolism, (2) interferonopathies, and (3) Gaucher disease. The finding of arterial calcification in early life should alert the clinician and prompt further genetic work-up to define the underlying genetic defect, to establish the correct diagnosis, and to enable appropriate therapy.